2019
DOI: 10.1007/s13197-019-03585-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and comparison of non-conventional extraction technologies for Citrus paradisi L. peels: a valorization approach

Abstract: The phenolics from grapefruit peel were obtained by ultrasound assisted extraction (UAE) and enzyme-assisted extraction (EAE). Extraction parameters were optimized using response surface methodology to maximize the yield of total phenolic content (TPC) and total flavonoid content (TFC). The optimized extracts from UAE and EAE were then compared with conventional solvent extraction for their TPC, TFC, antioxidant activity and phenolic composition. The best optimized conditions for UAE was obtained at 33.12 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Total phenolic, total flavonoid, naringin, and hesperidin contents of the extracts from pomelo peels were significantly affected by extraction techniques, in which the enzyme treatment had a higher impact than the ultrasound treatment. Nishad et al [13] also reported that EAE was more effective than UAE in extracting bioactive compounds of Citrus paradisi L. peels, similar to the results of this study. e more effective action of enzyme in releasing flavonoid compounds than ultrasonic wave might be due to the selective breakdown of the cell walls by enzyme compared to the random breakdown of cell walls by ultrasound.…”
Section: Effect Of Ultrasonic Time On Recovery Of Flavonoid Content Osupporting
confidence: 91%
See 2 more Smart Citations
“…Total phenolic, total flavonoid, naringin, and hesperidin contents of the extracts from pomelo peels were significantly affected by extraction techniques, in which the enzyme treatment had a higher impact than the ultrasound treatment. Nishad et al [13] also reported that EAE was more effective than UAE in extracting bioactive compounds of Citrus paradisi L. peels, similar to the results of this study. e more effective action of enzyme in releasing flavonoid compounds than ultrasonic wave might be due to the selective breakdown of the cell walls by enzyme compared to the random breakdown of cell walls by ultrasound.…”
Section: Effect Of Ultrasonic Time On Recovery Of Flavonoid Content Osupporting
confidence: 91%
“…e previous study also reported that the enzymes were used to disrupt the pectin-cellulose complex in citrus peel and released higher flavonoids (naringin) in the extracts [19]. Nishad et al [13] found that the optimized conditions for enzyme-assisted extraction of grapefruit peel were as follows: enzyme concentration of 0.9%, solvent-solid ratio of 40 ml/g, and extraction time of 4.81 h. In this study, the optimal extraction conditions were as follows: enzyme concentration of 2%, water-solid ratio of 40 ml/g, incubation temperature of 50°C, and extraction time of 60 min.…”
Section: Effect Of Enzyme Concentration On Recovery Of Flavonoid Contmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, the range of hesperidin content extract by UAE from grapefruit peel (0.62–1.09 mg/g) samples is consistent with the hesperidin content (0.71 mg/g) reported by Wu et al [ 58 ] from grapefruit peel treated by an ultrasound bath. However, the highest concentration of phenolic compounds, extracted from grapefruit peel ( Citrus paradisi L.) by UAE was published by Nishad et al [ 59 ]. They obtained 2116.71 mg GAE/100 g of TPC and 276.53 mg QE/100 g of TF and observed that TPC was affected ( p < 0.05) mainly by amplitude, simple-solvent ratio, and their interaction.…”
Section: Principal Non-conventional Technologies To Extract High Bmentioning
confidence: 99%
“…Solid-liquid extraction is the most widely used procedure for the extraction of organic substances in botanical materials due to its easy use, efficiency, and wide range of applicability. 18,19 Different organic solvents and their combination, as well as the combination of organic solvents and water, may be applied. Other factors such as pH, temperature, sample mass, and extraction time may be studied, as well as sequential steps in order to maximize the extraction.…”
Section: Introductionmentioning
confidence: 99%